Short-term to long-term employment effects of the Football World Cup 1974 in Germany - Florian Hagn; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2007)
This study demonstrates that the Football World Cup 1974 in Germany was not able to generate any short to long-term employment effects that were significantly different from zero. It is the first work to examine long-term employment effects of Football World Cup tournaments. It is also one of the first work to undertake a multivariate analysis of the employment effects of a major sporting event outside of the USA. In addition, this study does not arbitrarily determine the time period for the potential positive effects of a major sporting event but instead examines several alternative periods. Furthermore, the study tests for method sensitivity by analysing the data set in parallel with the approaches used in the studies of sporting events in the USA as well as in a fourth modifying estimation approach. In contrast to the conclusions reached in comparable studies, the results are not regarded as a clear refutation of the positive effects of major sporting events.
Keywords: L83; R53; R58; 330; Regional economics; sports economics; World Cup; Stadium Impact